The Reception of Aeschylus' Plays Through Shifting Models and Frontiers - Constantinidis, Stratos E. (Metaforms Ser, 2016)
The Reception of Aeschylus' Plays through Shifting Models and Frontiers -- Copyright -- Dedication -- Contents -- Acknowledgments -- List of Illustrations -- Notes on Contributors -- Introduction -- 1 Editing Aeschylus for a Modern Readership: Textual Criticism and Other Concerns -- 2 Aeschylus and His Afterlife in the Classical Period: "My Poetry Did Not Die with Me" -- 3 Prometheus Bound in Translation: "The True Promethean Fire" -- 4 Aeschylus' Seven against Thebes: War, Women, and the Hecht/Bacon Translation -- 5 Aeschylus in the Balance: Weighing Corpses and the Problem of Translation -- 6 Cognitive Theory and Aeschylus: Translating beyond the Lexicon -- 7 Aeschylus and Western Opera -- 8 Aeschylus' Cassandra in the Operas of Taneyev and Gnecchi -- 9 Pop Music Adaptations of Aeschylus' Plays: What Kind of Rock was Prometheus Fastened to? -- 10 Aeschylus as Postdramatic Analogue: "A Thing Both Cool and Fiery" -- 11 Voices of Trauma: Remaking Aeschylus' Agamemnon in the Twentieth Century -- 12 The Oresteia in Kannada: The Indian Context -- 13 Two Centuries, Two Oresteias, Two Remakes -- Bibliography -- Index.